Caspase 4 Overexpression as a Prognostic Marker in Clear Cell Renal Cell Carcinoma: A Study Based on the Cancer Genome Atlas Data Mining - Meng, Lingfeng; Tian, Zijian; Long, Xingbo; Diao, Tongxiang; Hu, Maolin; Wang, Miao; Zhang, Wei; Zhang, Yaoguang; Wang, Jianye; He, Yuhui (Frontiers in Genetics, 2021)
The dysregulation of caspase 4 (CASP4) expression is related to the occurrence, development, and outcome of many malignant tumors; however, its role in clear cell renal cell carcinoma (ccRCC) is unclear. Its expression in tumor tissues and relationship with the clinical prognosis of patients with ccRCC were investigated. Thus, the purpose of this study was to investigate the expression of CASP4, and its relationship with clinical prognosis, immune infiltration, and drug sensitivity in patients with ccRCC. Oncomine and The Cancer Genome Atlas databases were used to determine CASP4 mRNA expression in ccRCC and its association with prognosis. The correlation between CASP4 expression and ccRCC prognosis was evaluated using Kaplan–Meier analysis. Related pathways were obtained from The Cancer Genome Atlas database by gene set enrichment analysis (GSEA) and gene set variation analysis (GSVA). Additionally, the co-expression of the identified genes and CASP4 in ccRCC was assessed. Finally, we analyzed the proportion of tumor-infiltrating immune cells (TICs) by the CIBERSORT computational method and examined the CASP4 methylation and its relationship with drug sensitivity. Immunohistochemical analysis of 30 paired ccRCC and adjacent normal tissues confirmed in-silico results. CASP4 mRNA expression in ccRCC was significantly higher than that in normal tissues. The expression of CASP4 was positively correlated with clinicopathological features (clinical stage and pathological grade) and negatively correlated with the overall survival of patients with ccRCC. GSEA and GSVA showed that the genes in the CASP4-high expression group were mainly enriched in immune-related activities. CIBERSORT analysis of the proportion of TICs showed that the CD4 memory activated T cells were positively correlated with CASP4 expression. However, methylation analysis showed that the abnormal upregulation of CASP4 might be caused by hypomethylation. Finally, we found that the abnormal expression of CASP4 might be related to tumor drug resistance. Overall, our study shows that CASP4 is expressed at high levels in ccRCC and is an important factor affecting prognosis, making it a potential prognostic biomarker and therapeutic target for this disease.